Alternative futures for global biological invasions - Núria Roura-Pascual; Brian Leung; Wolfgang Rabitsch; Lucas Rutting; Joost Vervoort; Sven Bacher; Stefan Dullinger; Karl-Heinz Erb; Jonathan M. Jeschke; Stelios Katsanevakis; Ingolf Kühn; Bernd Lenzner; et al. (Sustainability Science, 2021)
Scenario analysis has emerged as a key tool to analyze complex and uncertain future socio-ecological developments. However, currently existing global scenarios (narratives of how the world may develop) have neglected biological invasions, a major threat to biodiversity and the economy. Here, we use a novel participatory process to develop a diverse set of global biological invasion scenarios spanning a wide range of plausible global futures through to 2050. We adapted the widely used “two axes” scenario analysis approach to develop four families of four scenarios each, resulting in 16 scenarios that were later clustered into four contrasting sets of futures. Our analysis highlights that socioeconomic developments and technological innovation have the potential to shape biological invasions, in addition to well-known drivers, such as climate and human land use change and global trade. Our scenarios partially align with the shared socioeconomic pathways created by the climate change research community. Several factors that drive differences in biological invasions were underrepresented in the shared socioeconomic pathways; in particular, the implementation of biosecurity policies. We argue that including factors related to public environmental awareness and technological and trade development in global scenarios and models is essential to adequately consider biological invasions in global environmental assessments and thereby obtain a more integrative picture of future social–ecological developments.

Drivers of future alien species impacts: An expert‐based assessment - Franz Essl; Bernd Lenzner; Sven Bacher; Sarah Bailey; Cesar Capinha; Curtis Daehler; Stefan Dullinger; Piero Genovesi; Cang Hui; Philip E. Hulme; Jonathan M. Jeschke; Stelios Katsanevakis; et al. (Global Change Biology, 2020)
Understanding the likely future impacts of biological invasions is crucial yet highly challenging given the multiple relevant environmental, socio‐economic and societal contexts and drivers. In the absence of quantitative models, methods based on expert knowledge are the best option for assessing future invasion trajectories. Here, we present an expert assessment of the drivers of potential alien species impacts under contrasting scenarios and socioecological contexts through the mid‐21st century. Based on responses from 36 experts in biological invasions, moderate (20%–30%) increases in invasions, compared to the current conditions, are expected to cause major impacts on biodiversity in most socioecological contexts. Three main drivers of biological invasions—transport, climate change and socio‐economic change—were predicted to significantly affect future impacts of alien species on biodiversity even under a best‐case scenario. Other drivers (e.g. human demography and migration in tropical and subtropical regions) were also of high importance in specific global contexts (e.g. for individual taxonomic groups or biomes). We show that some best‐case scenarios can substantially reduce potential future impacts of biological invasions. However, rapid and comprehensive actions are necessary to use this potential and achieve the goals of the Post‐2020 Framework of the Convention on Biological Diversity.

Investment and the Policy Process in Conservation Monitoring - JAMES N. SANCHIRICO; MICHAEL R. SPRINGBORN; MARK W. SCHWARTZ; ANGELA N. DOERR (Conservation Biology, 2014)
Despite decades of discussion and implementation, conservation monitoring remains a challenge. Many current solutions in the literature focus on improving the science or making more structured decisions. These insights are important but incomplete in accounting for the politics and economics of the conservation decisions informed by monitoring. Our novel depiction of the monitoring enterprise unifies insights from multiple disciplines (conservation, operations research, economics, and policy) and highlights many underappreciated factors that affect the expected benefits of monitoring. For example, there must be a strong link between the specific needs of decision makers and information gathering. Furthermore, the involvement of stakeholders other than scientists and research managers means that new information may not be interpreted and acted upon as expected. While answering calls for sharply delineated objectives will clearly add focus to monitoring efforts, for practical reasons, high‐level goals may purposefully be left vague, to facilitate other necessary steps in the policy process. We use the expanded depiction of the monitoring process to highlight problems of cooperation and conflict. We critique calls to invest in monitoring for the greater good by arguing that incentives are typically lacking. Although the benefits of learning accrued within a project (e.g., improving management) provide incentives for investing in some monitoring, it is unrealistic, in general, to expect managers to add potentially costly measures to generate shared benefits. In the traditional linear model of the role of science in policy decisions, monitoring reduces uncertainty and decision makers are rational, unbiased consumers of the science. However, conservation actions increasingly involve social conflict. Drawing insights from political science, we argue that in high‐conflict situations, it is necessary to address the conflict prior to monitoring. Las Inversiones y el Proceso de Políticas en el Monitoreo de la Conservación Sanchirico et al.